Heat / Cool . Energy Concepts, Principles, Installations - Hegger M. Manfred (Scale)
In order to build successfully today, careful consideration of energy efficiency has to be included in the design of a building. The second volume of the SCALE series, Heat \ Cool, illustrates strategies for balanced and appropriate energy-efficient design and looks at energy-efficiency factors as part of the scheme and detailed design of a building. The focus here is on the necessary services installations as well as the design of plan layouts and elevations. Using built projects as examples, the authors discuss the contribution—based on the respective climatic, topographic, and urban design context—that buildings can make through the choice of materials and design, the extent to which additional services installations are reguired for heating and cooling, and what combined measures are suitable for sustainable and holistic design. The authors cover currently available technical services for heating, ventilation, and cooling as well as ways in which the choice of materials and construction layout can support energy-efficiency in the building and optimise the lifecycle and flow of energy. Heat j Cool provides the basis for efficient and optimised conditioning of a building's interior climate and how this forms part of the architectural design.